Reconsidering the 'idea' of evidence in evidence-based policy and practice. Issue 3 (3rd July 2016) - Mullen, Edward J.
Abstract : Evidence-based policy and practice (EBP) has become an important social work conceptual framework. Yet, the core EBP concept, the concept of evidence, remains ill-defined. I propose a modification of the concept of evidence as applied to EBP effectiveness questions. As a basis for this reformulation ideas about evidence are examined from cross-disciplinary and multidisciplinary perspectives including epistemology, philosophy of science, evidence-science, and law. I propose that for EBP effectiveness questions: (1) to be considered 'relevant evidence' an explanatory connection between an intervention and an outcome must be established rather than a mere association; (2) the EBP definition of 'best available evidence' should include total available evidence (rather than a subset) about effectiveness, causal roles (i.e., mechanisms), and support factors and be inclusive of high-quality experimental and observational studies as well as high-quality mechanistic reasoning; (3) the familiar five-step EBP process should be expanded to include formulation of warranted, evidence-based arguments and that evidence appraisal be guided by three high level criteria of relevance, credibility, and strength rather than rigid evidence hierarchies; (4) comparative effectiveness research strategies, especially pragmatic controlled studies, hold promise for providing relevant and actionable evidence needed for policy and practice decision-making and successful implementation.